Polarizing plate with phase difference layer and image display device using the same

By designing a protective layer with high lead hardness in the auroral plate and a delay layer structure controlled at 32 μm or less, the problem that the auroral plate in the prior art is difficult to take into account both hardness and durability, and the high durability and deformation resistance of the image display device are achieved.

JP7654503B2Active Publication Date: 2025-04-01NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021130267
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-06
Publication Date
2025-04-01
Estimated Expiration
2041-08-06

AI Technical Summary

Technical Problem

The prior art is difficult to provide image display devices with high durability and deformation-resistant aurora plates while maintaining hardness.

Method used

An aurora plate structure is adopted with a protective layer, an aurora film and a retardation layer, wherein the lead hardness of the protective layer reaches 2B or more, the thickness of the retardation layer is controlled to 32 μm or less, and a matrix with a high elastic recovery rate is used in the protective layer.

Benefits of technology

The aurora plate is achieved in taking into account both hardness and deformation resistance, ensuring the durability and protective effect of the image display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654503000003
    Figure 0007654503000003
  • Figure 0007654503000004
    Figure 0007654503000004
  • Figure 0007654503000005
    Figure 0007654503000005
Patent Text Reader

Abstract

To provide a polarizing plate with retardation layers, which offers both hardness and deformation resistance.SOLUTION: A polarizing plate with retardation layers according to an embodiment of the present invention comprises a protective layer, a polarizing film, and retardation layers laminated in the described order, and has a pencil hardness of 2B or greater on a surface thereof on the protective layer side, where a laminated portion from the protective layer to the retardation layers has a thickness of 32 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate with a retardation layer and an image display device using the same. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices), are rapidly becoming widespread. A polarizing plate and a retardation plate are typically used in image display devices. In practice, a retardation layer-attached polarizing plate in which a polarizing plate and a retardation plate are integrated is widely used (e.g., Patent Document 1).

[0003] In recent years, the possibility of bending, flexing, folding, and rolling up image display devices using flexible substrates (e.g., resin substrates) has been considered, and a polarizing plate with a retardation layer that can accommodate this has been demanded. On the other hand, from the viewpoint of preventing scratches on image display devices, there has been a demand for improving the hardness of the polarizing plate with a retardation layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above, and a main object of the present invention is to provide a retardation layer-attached polarizing plate having both hardness and durability against deformation. [Means for solving the problem]

[0006] The polarizing plate with a retardation layer according to an embodiment of the present invention has a protective layer, a polarizing film, and a retardation layer in that order, the surface hardness of the protective layer side is a pencil hardness of 2B or more, and the thickness of the laminated portion from the protective layer to the retardation layer is 32 μm or less. In one embodiment, the protective layer includes a base material having an indentation elastic recovery rate of 67% or less. In one embodiment, the ratio of the base material to the thickness from the center of the laminated portion to the surface of the protective layer is 65% or more. In one embodiment, the protective layer includes a portion having an indentation hardness of 0.35 GPa or more. In one embodiment, the protective layer has a thickness of 12 μm or more and less than 20 μm. In one embodiment, the protective layer includes a hard coat layer having a thickness of 5 μm or less. In one embodiment, the retardation layer is a layer in which a liquid crystal compound is aligned and fixed. In one embodiment, the protective layer has a moisture permeability of 200 g / m at 40° C. and 92% RH. 2 Includes substrates less than 24h old. According to another aspect of the present invention, there is provided an image display device, the image display device having the above-mentioned retardation layer-attached polarizing plate. Effect of the Invention

[0007] According to the embodiment of the present invention, in a retardation layer-attached polarizing plate, it is possible to achieve both hardness and durability against deformation. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view showing an outline of a configuration of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view showing an example of a configuration of a protective layer of the retardation layer-attached polarizing plate shown in FIG. [Diagram 3] FIG. 4 is a diagram for explaining the ratio of the center of a laminated portion to the base material. [Figure 4] FIG. 1 is a diagram for explaining the indentation direction in a nanoindenter test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to these embodiments. In addition, in order to clarify the description, the width, thickness, shape, etc. of each part may be shown in a schematic manner compared to the embodiment, but it is merely an example and does not limit the interpretation of the present invention.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0011] FIG. 1 is a schematic cross-sectional view showing an outline of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 100 has a polarizing plate 10 including a polarizing film 11 and a protective layer 12 arranged on one side of the polarizing film 11, and a retardation layer 20. Specifically, the retardation layer-attached polarizing plate 100 has a protective layer 12, a polarizing film 11, and a retardation layer 20 in this order. The retardation layer 20 can function as a protective layer for the polarizing film 11. With this configuration, the thickness of the retardation layer-attached polarizing plate described below can be satisfactorily achieved. The retardation layer-attached polarizing plate 100 is typically arranged in an image display device such that the polarizing plate 10 is closer to the viewer than the retardation layer 20. In one embodiment, the protective layer 12 is located on the outermost surface of the image display device.

[0012] In the illustrated example, the retardation layer 20 has a laminated structure including a first retardation layer 21 and a second retardation layer 22. However, unlike the illustrated example, the retardation layer 20 may have a laminated structure of three or more layers, or may be a single layer.

[0013] Each member constituting the retardation layer polarizing plate may be laminated via any suitable adhesive layer (not shown). Specific examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. For example, the protective layer 12 is attached to the polarizing film 11 via an adhesive layer (preferably using an active energy ray curable adhesive). For example, the retardation layer 20 is attached to the polarizing film 11 via an adhesive layer (preferably using an active energy ray curable adhesive). As shown in the figure, when the retardation layer 20 has a laminated structure of two or more layers, the retardation layers are attached to each other, for example, via an adhesive layer (preferably using an active energy ray curable adhesive). The thickness of the adhesive layer is preferably 0.4 μm or more, more preferably 0.4 μm to 3.0 μm, and even more preferably 0.6 μm to 1.5 μm.

[0014] Although not shown, an adhesive layer may be provided on the side of the retardation layer 20 on which the polarizing film 11 is not disposed. This adhesive layer allows, for example, the retardation layer-attached polarizing plate 100 to be attached to an image display panel included in an image display device. In practice, a release film (separator) is attached to the surface of this adhesive layer. The release film may be temporarily attached until the retardation layer-attached polarizing plate is used. The use of the release film, for example, protects the adhesive layer and enables the polarizing plate to be formed into a roll.

[0015] The retardation layer-attached polarizing plate may be in a long shape or a sheet shape. Here, "long" refers to a long and narrow shape whose length is sufficiently long relative to its width, for example, whose length is 10 times or more, preferably 20 times or more, relative to its width. The long retardation layer polarizing plate can be wound into a roll.

[0016] The surface hardness of the protective layer 12 (polarizing plate 10) side of the retardation layer-attached polarizing plate is, in pencil hardness, 2B or more, and preferably B or more. On the other hand, the surface hardness of the protective layer 12 side is, for example, 4H or less in pencil hardness.

[0017] The thickness of the laminated portion from the protective layer 12 to the retardation layer 20 (sometimes simply referred to as the "thickness of the retardation layer-attached polarizing plate") is 32 μm or less, and preferably 31 μm or less. With such a thickness, it is possible to achieve a remarkable durability against deformation (e.g., bending resistance) while satisfying the above-mentioned surface hardness. Specifically, it is possible to reduce the expansion and contraction caused by deformation (e.g., bending) and suppress the occurrence of breakage (e.g., interfacial breakage). It also contributes to making the image display device thinner, and for example, it may be possible to mount a component (battery, etc.) to accommodate a larger screen. On the other hand, the thickness of the retardation layer-attached polarizing plate is, for example, 25 μm or more.

[0018] The thickness of the retardation layer-attached polarizing plate includes the thickness of the adhesive layer. Specifically, the thickness of the adhesive layer that may be disposed between the protective layer and the polarizing film, the adhesive layer that may be disposed between the polarizing film and the retardation layer, and the adhesive layer that may be disposed between the retardation layers when the retardation layer has a laminated structure are also included. Note that the thickness of the retardation layer-attached polarizing plate does not include the adhesive layer for adhering the retardation layer-attached polarizing plate to an external adherend such as a panel or glass.

[0019] A. Polarizing plate The polarizing plate includes a polarizing film and a protective layer. Typically, the polarizing plate can be obtained by laminating the polarizing film and the protective layer via an adhesive layer.

[0020] A-1. Polarizing film The polarizing film is typically a resin film containing a dichroic substance (e.g., iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films.

[0021] The thickness of the polarizing film is preferably 12 μm or less, more preferably 10 μm or less, and further preferably 8 μm or less, while the thickness of the polarizing film is preferably 1 μm or more.

[0022] The polarizing film preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizing film is, for example, 41.5% to 48.0%, and preferably 42.0% to 46.0%. The polarization degree of the polarizing film is, for example, 90.0% or more, preferably 99.0% or more, and more preferably 99.9% or more.

[0023] The polarizing film may be produced by any appropriate method. Specifically, the polarizing film may be produced from a single-layer resin film or may be produced using a laminate of two or more layers.

[0024] The method for producing a polarizing film from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, etc. Such a production method is well known and commonly used in the art, so a detailed description thereof will be omitted.

[0025] The polarizing film obtained by using the laminate can be produced, for example, by using a laminate of a resin substrate and a resin film or resin layer (typically, a PVA-based resin layer). Specifically, the polarizing film can be produced by applying a PVA-based resin solution to a resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizing film. In this embodiment, preferably, a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, preferably, the laminate is subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of the present embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and high optical properties can be achieved. In addition, by simultaneously increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing or stretching process can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of PVA molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by shrinking the laminate in the width direction by the drying shrinkage treatment, high optical properties can be achieved. A polarizing plate can be obtained by laminating a protective layer on the peeled surface obtained by peeling the resin substrate from the obtained resin substrate / polarizing film laminate, or on the surface opposite to the peeled surface. Details of such a method for producing a polarizing film are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.

[0026] A-2.Protective layer FIG. 2 is a cross-sectional view showing an example of the configuration of the protective layer of the retardation layer-attached polarizing plate shown in FIG. 1. The protective layer 12 has a substrate (film) 12a and a hard coat (HC) layer 12b formed on the substrate 12a. By providing the hard coat layer 12b, the surface hardness of the protective layer side can be achieved well. The retardation layer-attached polarizing plate is typically disposed on the viewing side of an image display device, and the hard coat layer 12b is disposed on the viewing side of the substrate 12a. The hard coat layer 12b may function as another functional layer, such as an anti-reflection layer, an anti-sticking layer, or an anti-glare layer.

[0027] The thickness of the protective layer is preferably less than 20 μm, more preferably 18 μm or less, whereas the thickness of the protective layer is preferably 12 μm or more, more preferably 14 μm or more.

[0028] The moisture permeability of the protective layer at 40° C. and 92% RH is preferably 200 g / m 2 Less than 24h, 150g / m 2 - 24 hours or less, 100g / m 2 - 24h or less, 50g / m 2 The first protective layer 12 may have a moisture permeability of, for example, 1 g / m 2 at 40° C. and 92% RH. 2 -24 hours or more.

[0029] The indentation elastic recovery rate of the substrate is preferably 67% or less, more preferably 65% ​​or less, and may be 60% or less. By using such a substrate, the durability against deformation (e.g., bending resistance) can be improved. Specifically, the stress caused by deformation (e.g., bending) can be dispersed to suppress the occurrence of destruction (e.g., interfacial destruction). In addition, the adhesion with the hard coat layer can be excellent. Meanwhile, the indentation elastic recovery rate of the substrate is, for example, 35% or more.

[0030] The thickness of the substrate is, for example, 10 μm to 16 μm, preferably 11 μm to 15 μm, and more preferably 12 μm to 14 μm.

[0031] The ratio of the base material to the thickness from the center of the laminated portion (polarizing plate with retardation layer) from the protective layer to the retardation layer to the protective layer surface is preferably 65% ​​or more, more preferably 75% or more. On the other hand, the ratio of the base material to the thickness from the center of the laminated portion (polarizing plate with retardation layer) from the protective layer surface to the protective layer surface is preferably 90% or less.

[0032] FIG. 3 is a diagram for explaining the center of the laminated portion (polarizing plate with retardation layer) and the ratio of the substrate. In FIG. 3, hatching is omitted. The laminated portion (polarizing plate with retardation layer) 102 has a protective layer 12 including a hard coat layer 12b and a substrate 12a, an adhesive layer 52, a polarizing film 11, an adhesive layer 54, a first retardation layer 21, an adhesive layer 56, and a second retardation layer 22, in this order. As described above, in the thickness direction, the ratio of the thickness t of the substrate 12a to the distance d from the center 103 of the laminated portion 102 to the surface 13 of the protective layer 12 is preferably 65% ​​or more, more preferably 75% or more. In one embodiment, the above ratio is controlled by adjusting the thickness of the hard coat layer.

[0033] The substrate may be any suitable film that can be used as a protective layer for the polarizing film. Specific examples of materials that are the main components of such films include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other transparent resins. Preferably, the material that constitutes the substrate is at least one selected from polycarbonate-based resins and cycloolefin-based resins.

[0034] The indentation hardness of the hard coat layer is preferably 0.35 GPa or more, more preferably 0.4 GPa or more, and even more preferably 0.45 GPa or more. On the other hand, the indentation hardness of the hard coat layer is, for example, 0.70 GPa or less. On the other hand, the indentation elastic recovery rate of the hard coat layer is preferably 70% or more, more preferably 75% or more. On the other hand, the indentation elastic recovery rate of the hard coat layer is, for example, 95% or less.

[0035] The thickness of the hard coat layer is preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less. By providing such a hard coat layer, it is possible to achieve durability against deformation (e.g., bending resistance) while satisfying the above-mentioned surface hardness. On the other hand, the thickness of the hard coat layer is, for example, 1 μm or more.

[0036] The hard coat layer is typically formed by applying a hard coat layer-forming material to the substrate and curing the applied layer. The hard coat layer-forming material typically includes a curable compound as a layer-forming component. The curing mechanism of the curable compound may be, for example, a thermosetting type or a photocurable type. The curable compound may be, for example, a monomer, an oligomer, or a prepolymer. Preferably, a polyfunctional monomer or oligomer is used as the curable compound. The polyfunctional monomer or oligomer may be, for example, a monomer or oligomer having two or more (meth)acryloyl groups, a urethane (meth)acrylate or an oligomer of a urethane (meth)acrylate, an epoxy-based monomer or oligomer, or a silicone-based monomer or oligomer.

[0037] The hard coat layer forming material may contain any suitable additive. Examples of additives include polymerization initiators, leveling agents, antiblocking agents, dispersion stabilizers, thixotropic agents, antioxidants, UV absorbers, defoamers, thickeners, dispersants, surfactants, catalysts, fillers, lubricants, antistatic agents, etc. The type, combination, content, etc. of additives can be appropriately set according to the purpose and desired characteristics.

[0038] When the curable compound is a thermosetting compound, the heating temperature is, for example, 60° C. to 140° C., and preferably 60° C. to 100° C. When the curable compound is a photocurable compound, the curing treatment is typically carried out by ultraviolet irradiation. The integrated light amount of the ultraviolet irradiation is, for example, 100 mJ / cm 2 2 ~300mJ / cm 2 The ultraviolet irradiation and heating may be combined. In this case, typically, the coating film is heated and then irradiated with ultraviolet rays. The heating temperature is as described above with respect to the thermosetting curable compound.

[0039] B. Retardation layer The thickness of the retardation layer depends on its structure (whether it is a single layer or has a laminated structure), but is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 7 μm or less. On the other hand, the thickness of the retardation layer is, for example, 0.5 μm or more. In addition, when the retardation layer has a laminated structure, the "thickness of the retardation layer" means the total thickness of each retardation layer. Specifically, the "thickness of the retardation layer" does not include the thickness of the adhesive layer.

[0040] As the retardation layer, a liquid crystal compound alignment solidified layer (liquid crystal alignment solidified layer) is preferably used. By using a liquid crystal compound, for example, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. Therefore, a polarizing plate with a retardation layer can be significantly thinned. In this specification, the "alignment solidified layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. Note that the "alignment solidified layer" is a concept that includes an alignment hardened layer obtained by hardening a liquid crystal monomer as described later. In the retardation layer, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the retardation layer (homogeneous alignment).

[0041] The liquid crystal alignment solidified layer can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.

[0042] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0043] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.

[0044] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.

[0045] As described above, the retardation layer may be a single layer or may have a laminated structure of two or more layers.

[0046] Unlike the illustrated example, when the retardation layer is a single layer, the retardation layer can function as a λ / 4 plate. Specifically, the Re(550) of the retardation layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 160 nm. The thickness of the retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the retardation layer is the above-mentioned liquid crystal alignment solidified layer, the thickness is, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizing film is preferably 40° to 50°, more preferably 42° to 48°, and further preferably 44° to 46°. In addition, it is preferable that the retardation layer exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light.

[0047] As shown in the figure, when the retardation layer 20 has a laminated structure, the retardation layer 20 has a two-layer laminated structure in which, for example, a first retardation layer (H layer) 21 and a second retardation layer (Q layer) 22 are arranged in order from the polarizing plate 10 side. The H layer can typically function as a λ / 2 plate, and the Q layer can typically function as a λ / 4 plate. Specifically, Re(550) of the H layer is preferably 200 nm to 300 nm, more preferably 220 nm to 290 nm, and even more preferably 230 nm to 280 nm; Re(550) of the Q layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and even more preferably 110 nm to 150 nm. The thickness of the H layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. When the H layer is the above-described liquid crystal alignment cured layer, its thickness is, for example, 2.0 μm to 4.0 μm. The thickness of the Q layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the Q layer is the above-described liquid crystal alignment cured layer, its thickness is, for example, 0.5 μm to 2.5 μm. In the present embodiment, the angle formed by the slow axis of the H layer and the absorption axis of the polarizing film is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 12° to 16°; the angle formed by the slow axis of the Q layer and the absorption axis of the polarizing film is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 72° to 76°. When the retardation layer 20 has a laminated structure, each layer (for example, the H layer and the Q layer) may exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light.

[0048] The retardation layer (when having a laminated structure, at least one layer) typically exhibits a refractive index characteristic showing a relationship of nx > ny = nz. Note that “ny = nz” includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3.

[0049] As described above, the retardation layer is preferably a liquid crystal alignment solidified layer. The liquid crystal compound may be, for example, a liquid crystal compound (nematic liquid crystal) whose liquid crystal phase is a nematic phase. For example, a liquid crystal polymer or a liquid crystal monomer may be used as such a liquid crystal compound. The liquid crystal compound may exhibit liquid crystallinity by either lyotropic or thermotropic mechanism. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.

[0050] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the liquid crystal monomer can be polymerized or crosslinked (i.e., cured) to fix the alignment state of the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other to fix the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.

[0051] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0052] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. As the liquid crystal monomer, a nematic liquid crystal monomer is preferable.

[0053] C. Preparation of polarizing plate with retardation layer The polarizing plate with a retardation layer according to the embodiment of the present invention can be obtained by laminating the above-mentioned polarizing plate and the above-mentioned retardation layer. The lamination of the polarizing plate and the retardation layer is performed, for example, while conveying them by rolls (so-called roll-to-roll). The lamination is typically performed by transferring a liquid crystal alignment solidified layer formed on a substrate. As shown in the figure, when the retardation layer has a laminated structure, each retardation layer may be laminated (transferred) sequentially onto the polarizing plate, or a laminate in which retardation layers are previously laminated together may be laminated (transferred) onto the polarizing plate.

[0054] D. Image display device The retardation layer-attached polarizing plate can be applied to an image display device. Accordingly, an image display device according to an embodiment of the present invention has the retardation layer-attached polarizing plate. EXAMPLES

[0055] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thickness and moisture permeability are values ​​measured by the following measuring methods. Furthermore, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight. 1. Thickness The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). 2. Moisture permeability The moisture permeability was determined by the cup method (JIS Z 0208).

[0056] [Example 1] (Preparation of polarizing plate) As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of this resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a weight ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizing film would be the desired value (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizing film having a thickness of 5.4 μm was formed on the resin substrate, and a laminate having a resin substrate / polarizing film structure was obtained.

[0057] A polycarbonate film having a hard coat (HC) layer formed thereon was attached as a protective layer to the polarizing film side of the obtained laminate via an ultraviolet-curable adhesive (thickness after curing: 1.5 μm).Then, the resin substrate was peeled off from the polarizing film to obtain a polarizing plate having a structure of HC layer / polycarbonate film / adhesive layer / polarizing film. In addition, the polycarbonate film on which the HC layer was formed (moisture permeability at 40°C and 92% RH: 170 g / m 2 24h) was performed by applying the hard coat layer forming material A shown below to a polycarbonate film (thickness 13 μm) shown below, heating it at 60 °C for 1 minute, and then irradiating the coating layer after heating with a high-pressure mercury lamp with an integrated light quantity of 250 mJ / cm 2 The coating layer was cured by irradiating it with ultraviolet light of 1000 ohms to form a HC layer having a thickness of 2 μm.

[0058] (Preparation of polycarbonate films) 81.98 parts by mass of isosorbide, 47.19 parts by mass of tricyclodecane dimethanol, 175.1 parts by mass of diphenyl carbonate, and 0.979 parts by mass of a 0.2% by mass aqueous solution of cesium carbonate as a catalyst were charged into a reaction vessel, and as the first step of the reaction, the heating tank temperature was heated to 150°C under a nitrogen atmosphere, and the raw materials were dissolved while stirring as necessary (approximately 15 minutes). Next, the pressure was changed from normal pressure to 13.3 kPa, and the temperature of the heating bath was increased to 190° C. over one hour while the generated phenol was discharged outside the reaction vessel. After the entire reaction vessel was kept at 190°C for 15 minutes, in the second step, the pressure inside the reaction vessel was set to 6.67 kPa, the temperature of the heating bath was raised to 230°C in 15 minutes, and the phenol generated was removed from the reaction vessel. As the stirring torque of the stirrer increased, the temperature was raised to 250°C in 8 minutes, and the pressure inside the reaction vessel was allowed to reach 0.200 kPa or less in order to remove the phenol generated further. After the predetermined stirring torque was reached, the reaction was terminated, and the reaction product generated was extruded into water to obtain pellets of polycarbonate copolymer. The obtained pellets were subjected to a film-forming apparatus equipped with a single-screw extruder (manufactured by Isuzu Chemical Engineering Co., Ltd., screw diameter 25 mm, cylinder set temperature: 220°C), a T-die (width 200 mm, set temperature: 220°C), a chill roll (set temperature: 120-130°C) and a winder to obtain a polycarbonate film.

[0059] (Preparation of Hard Coat Layer Forming Material A) Hard coat layer forming material A was prepared by mixing 80 parts of urethane acrylate resin (Mitsubishi Chemical Corporation, "UT-7314"), 20 parts of urethane acrylate resin (DIC Corporation, "ELS888"), 0.1 parts of a leveling agent (Kyoeisha Chemical Co., Ltd., "LE-303") and 3 parts of a photopolymerization initiator (IGM Resins Italia Srl, "OMNIRAD907") and diluting with cyclopentanone and methyl isobutyl ketone to a solids concentration of 30%.

[0060] (Preparation of Retardation Layer) A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka]

[0061] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth to perform an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizing film when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90°C for 2 minutes. The liquid crystal layer thus formed was then irradiated with 1 mJ / cm using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal with light, forming a liquid crystal alignment layer A (H layer) on the PET film. The liquid crystal alignment layer A had a thickness of 2.5 μm and an in-plane retardation Re(550) of 270 nm. Furthermore, the liquid crystal alignment layer A showed a refractive index characteristic of nx>ny=nz.

[0062] A liquid crystal alignment layer B (Q layer) was formed on a PET film in the same manner as above, except that the coating thickness was changed and the alignment treatment direction was set to a 75° direction from the viewing side with respect to the absorption axis direction of the polarizing film. The liquid crystal alignment layer B had a thickness of 1.5 μm and an in-plane retardation Re(550) of 140 nm. Furthermore, the liquid crystal alignment layer B showed a refractive index characteristic of nx>ny=nz.

[0063] (Preparation of polarizing plate with retardation layer) The obtained liquid crystal alignment solidified layer A (H layer) and liquid crystal alignment solidified layer B (Q layer) were transferred in this order to the polarizing film side of the obtained polarizing plate. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizing film and the slow axis of the alignment solidified layer A was 15°, and the angle between the absorption axis of the polarizing film and the slow axis of the alignment solidified layer B was 75°. Each transfer was performed via an ultraviolet-curing adhesive (thickness after curing: 1 μm) while being transported by rolls. In this way, a polarizing plate with a retardation layer was obtained.

[0064] [Example 2] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the thickness of the HC layer was 5 μm.

[0065] [Example 3] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that a COP film having an HC layer formed thereon was used as the protective layer. The COP film on which the HC layer was formed was a cycloolefin-based unstretched film (manufactured by Zeon Corporation, thickness 13 μm, moisture permeability 35 g / m at 40° C. and 92% RH). 2 24h), the hard coat layer forming material B shown below was applied and heated at 60°C for 1 minute, and the applied layer after heating was then exposed to a high pressure mercury lamp with an integrated light intensity of 250mJ / cm 2 The coating layer was cured by irradiating it with ultraviolet light of 1000 ohms to form a HC layer having a thickness of 2 μm.

[0066] (Preparation of Hard Coat Layer Forming Material B) 60 parts of urethane acrylate resin (DIC Corporation, "ELS888"), 60 parts of urethane acrylate resin (DIC Corporation, "RS28-605"), 0.03 parts of a leveling agent (DIC Corporation, "GRANDIC PC4100"), and 3.9 parts of a photopolymerization initiator (IGM Resins Italia Srl, "OMNIRAD184") were mixed and diluted with ethyl acetate to a solids concentration of 25%, to prepare hard coat layer forming material B.

[0067] [Comparative Example 1] As a protective layer, an acrylic film having a lactone ring structure (thickness: 20 μm, moisture permeability at 40° C. and 92% RH: 150 g / m 2 A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the 100-μm thick film (1.0 x 100 mm) was used.

[0068] [Comparative Example 2] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the thickness of the HC layer was 7 μm.

[0069] [Comparative Example 3] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that an acrylic film having an HC layer formed thereon was used as the protective layer. The acrylic film on which the HC layer was formed was prepared by applying the hard coat layer forming material C shown below to the acrylic film having the lactone ring structure and heating it at 60° C. for 1 minute, and then irradiating the applied layer with an integrated light quantity of 250 mJ / cm 2 from a high-pressure mercury lamp. 2 The coating layer was cured by irradiating it with ultraviolet light of 1000 ohms to form a HC layer having a thickness of 5 μm.

[0070] (Preparation of Hard Coat Layer Forming Material C) Hard coat layer forming material C was prepared by mixing 100 parts of urethane acrylate resin (DIC Corporation, "UNIDIC 17-806"), 0.01 parts of a leveling agent (DIC Corporation, product name "GRANDIC PC4100"), and 3 parts of a photopolymerization initiator (IGM Resin Italia Srl, "OMNIRAD907") and diluting the mixture with ethyl acetate and propylene glycol monomethyl ether to a solids concentration of 36%.

[0071] [Comparative Example 4] The COP film was treated with a cycloolefin-based unstretched film (manufactured by Zeon Corporation, thickness 25 μm, moisture permeability 20 g / m at 40°C and 92% RH). 2 A polarizing plate with a retardation layer was obtained in the same manner as in Example 3, except that the heating period was changed to 24 h.

[0072] [Reference example 1] A retardation layer-attached polarizing plate was obtained in the same manner as in Example 1, except that the polarizing plate shown below was used as the polarizing plate.

[0073] (Preparation of polarizing plate) A long roll of 30 μm-thick polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000") was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine, while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes in that order, and finally a drying process to produce a 12 μm-thick polarizing film. The above swelling treatment was performed by stretching the film 2.2 times while treating with pure water at 20°C. Next, the dyeing treatment was performed by stretching the film 1.4 times while treating it in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, with the iodine concentration adjusted so that the single transmittance of the resulting polarizing film was 45.0%. Next, the crosslinking treatment was performed in two stages, and the first stage was stretched 1.2 times while treating it in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The aqueous solution for the first stage crosslinking treatment had a boric acid content of 5.0% by weight and a potassium iodide content of 3.0% by weight. The second stage crosslinking treatment was performed by stretching the film 1.6 times while treating it in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution for the second stage crosslinking treatment had a boric acid content of 4.3% by weight and a potassium iodide content of 5.0% by weight. Next, the film was washed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the washing treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain a polarizing film.

[0074] A TAC film with a hard coat (HC) layer formed thereon and a 20 μm-thick TAC film were bonded to both sides of the obtained polarizing film via a polyvinyl alcohol-based adhesive, respectively, to obtain a polarizing plate having a structure of HC layer / TAC film / adhesive layer / polarizing film / adhesive layer / TAC film. In addition, the TAC film on which the HC layer was formed (moisture permeability at 40°C and 92% RH: 800 g / m 2 24h) was performed by applying the above hard coat layer forming material C to a TAC film (thickness 25 μm) and heating it at 60°C for 1 minute, and then irradiating the coating layer after heating with a high-pressure mercury lamp with an integrated light quantity of 250 mJ / cm 2 The coating layer was cured by irradiating it with ultraviolet light of 1000 ohms to form a HC layer having a thickness of 7 μm.

[0075] The following evaluations were carried out for the Examples and Comparative Examples. The evaluation results are summarized in Table 1. <Evaluation> 1. Indentation hardness and indentation elastic recovery rate The hardness of the protective layer (outermost layer) and the elastic recovery rate of the protective layer (HC layer and film) were measured by a nanoindenter test. Specifically, the obtained polarizing plate with a retardation layer was cut into a size of 20 mm vertically (absorption axis direction of the polarizing film, MD direction) and 20 mm horizontally (TD direction) using a cutter to obtain a test piece. The cut surface of the obtained test piece was cut using a microtome, and it was placed in an environment of 23°C and 55% RH for 3 hours (humidity control), and then measured using a nanoindenter. For the measurement using the nanoindenter, a "Triboindenter" manufactured by Hysitron Inc. was used, and a Berkovich (triangular pyramid) was used as the indenter. Under the conditions of an indentation speed of 20 nm / sec and an indentation depth of 100 nm, the load-displacement curve was measured by indenting from the cut surface as shown in Figure 4, and the indentation hardness and indentation elastic recovery rate were calculated. 2.Surface hardness The pencil hardness of the protective layer side of the obtained retardation layer-attached polarizing plate was measured under a load of 500 g in accordance with the pencil hardness test of JIS K5600-5-4. 3. Flexibility The evaluation was performed by the MIT test. The MIT test was performed according to JIS P 8115. Specifically, the obtained polarizing plate with a retardation layer was cut into a size of 15 cm in length and 15 mm in width with a cutter so that the absorption axis direction of the polarizing film was the length direction to obtain a test piece. The test piece was attached to an MIT folding fatigue tester (manufactured by Tester Sangyo Co., Ltd., BE-202 type) (load: 200 gf, clamp R: 0.38 mm), and repeatedly folded under the conditions of a folding speed of 175 times / min and a folding angle of 135°, and the number of foldings at which the measurement sample broke was obtained to evaluate the flexural resistance. 4. Adhesion The adhesion was evaluated by a cross-cut peel test. The cross-cut peel test was performed according to JIS K-5400. Specifically, 11 × 11 cuts were made at 1 mm intervals on the surface of the protective layer side of the obtained retardation layer-attached polarizing plate, reaching the substrate (film), using a cutter guide and a cutter knife to form 100 cross-cuts, and then an adhesive tape (manufactured by Nichiban Co., Ltd.) was pressed and instantaneously peeled off at an angle of 90°, and the number of cross-cuts from which the HC layer peeled off (pieces / 100 pieces) was counted to evaluate adhesion.

[0076] [Table 1]

[0077] The polarizing plate with a retardation layer of the embodiment had both hardness and durability. In the MIT test of Comparative Example 2-4, the interface between the HC layer and the film was broken before the number of folding times reached 1000. In the cross-cut peel test of Comparative Example 3, peeling occurred at the interface between the HC layer and the film. [Industrial Applicability]

[0078] The retardation layer-attached polarizing plate according to the embodiment of the present invention is used in an image display device, and is particularly suitable for use in a curved, bent, foldable, or rollable image display device. Representative examples of the image display device include a liquid crystal display device, an organic EL display device, and an inorganic EL display device. [Explanation of symbols]

[0079] 10 Polarizing plate 11 Polarizing film 12 Protective layer 20 Retardation layer 21 First retardation layer 22 Second retardation layer 100 Polarizing plate with retardation layer

Claims

1. The polarizing film has a protective layer, a polarizing film, and a retardation layer in this order. an adhesive is present between the protective layer and the polarizing film, and between the polarizing film and the retardation layer; the protective layer includes a hard coat layer formed of a substrate and a curable compound, The retardation layer is a layer in which a liquid crystal compound is aligned and solidified, The thickness of the protective layer is 12 μm or more and less than 20 μm, The thickness of the substrate is 10 μm or more and 14 μm or less, The indentation elastic recovery rate of the substrate is 67% or less, The thickness of the hard coat layer is 5 μm or less, The surface hardness of the protective layer side is 2B or more in terms of pencil hardness, The thickness of the laminated portion from the protective layer to the retardation layer is 32 μm or less. Polarizing plate with retardation layer.

2. 2. The polarizing plate with a retardation layer according to claim 1, wherein the ratio of the base material to the thickness from the center of the laminated portion to the surface of the protective layer is 65% or more.

3. 3. The polarizing plate with a retardation layer according to claim 1, wherein the protective layer includes a portion having an indentation hardness of 0.35 GPa or more.

4. The protective layer has a moisture permeability of 200 g / m at 40° C. and 92% RH. 2 The retardation layer-attached polarizing plate according to claim 1 , comprising a substrate having a thickness of less than 24 h.

5. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .

Citation Information

Patent Citations

  • Polarizing plate with retardation layer and image display device

    JP2018205663A

  • Electroluminescent display device

    JP2019169470A

  • Laminate and image display device

    JP2021111363A

  • Retardation film and optical device using the same

    JP3325560B2

  • Polarizing plate and image display device comprising the same

    US20180059300A1